Kiki Strike : inside the shadow city - Miller, Kirsten, 1973- (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Pub., 2007)
Life becomes more interesting for Ananka Fishbein when, at the age of twelve, she discovers an underground room in the park across from her New York City apartment and meets a mysterious girl called Kiki Strike who claims that she, too, wants to explore the subterranean world.